15 Antitumour activity of glucosamine hydrochloride in vitro. (1st December 2016) - Jiang, Tao; Wang, Liang; Zhao, Xi
Abstract : Background: Glucosamine hydrochloride, a natural biopolymer present in the daily diet, has various biological activities including antitumour properties and protective effects against pathogens. Early studies showed that daily administration of a derivative of glucosamine induced proliferation of leukemia cells and prolonged overall survival in mice; importantly, no toxicity was associated with the glucosamine treatment. However, the potential mechanism of the antitumour effect is unknown. This study aimed to investigate the inhibitory mechanism and effect of glucosamine on human gastric carcinoma cells in vitro. Methods: Gastric carcinoma MKN-45 cells were exposed to 0, 100, 500 and 1000 µg/mL glucosamine hydrochloride for 72 hours, and then the viability and proliferation of gastric carcinoma cells in vitro was measured using the MTT (3-(4.5-dimethylthiazol-2-yl)-2.5-diphenyltetrazolium bromide) assay. Quantitative gene expression of MMP-2 and -3 was determined by real-time polymerase chain reaction. Protein level was analyzed using an enzyme-linked immunosorbent assay (ELISA). Results: Glucosamine hydrochloride has a significant inhibitory antitumour effect on MKN-45 cells in vitro. The cell viability of MKN-45 cells treated with different concentrations of glucosamine hydrochloride rose continuously from 24 to 72 hours compared with the untreated control. MKN-45 cells were inhibited by 54% by 500 µg/mL glucosamine hydrochloride and by 85% by 1000 µg/mL glucosamine hydrochloride. Administration of 500 µg/mL glucosamine hydrochloride resulted in a significant decrease in MMP-2 and MMP-3 expression of about 79% and 70%, respectively, in MKN-45 cells. Conclusions: In this study, we showed that the antitumour activity of glucosamine hydrochloride significantly suppresses MKN-45 cells in vitro. This effect was shown by inhibitory gene expression of MMP-2 and -3. Acknowledgments: This research was financially supported by Zhuhai College of Jilin University.